표고버섯 산업의 동향과 관측사업 구상 - 석현덕 (한국농촌경제연구원, 2003)
The Ttrend of Shiitake Industry and the Plan of It's Outlook Project Since the forestry product outlook project provides informations on forest product prices and quantities which are essential informations for improving farm planning and marketing strategies, the outlook project could be crucial for stabilizing the forest products market and improving farm household income. The Shiitake industry is the one of highly capital and technology-intensive industries among forest product industries, and the management profits of the Shiitake industry are highly depend on production timing, the outlook project for the industry can be largely effective. The outlook project for Shiitake industry will begin on the March of 2004. The Monthly Shiitake Outlook will be issued as periodicals and distributed to the growers. Researchers: Seok Hyun-Deok and Min Kyung-Taek E-mail Address: hdseok@krei.re.kr, minkt@krei.re.kr
Keywords: 표고; 버섯; 표고버섯; 버섯산업; 관측사업